Pengaruh Pengungkapan Corporate Social Responsibility, Struktur Modal, dan Financial Distress terhadap Return Saham Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2017-2021 - Fathihani; Randyantini, Vely; Saputri, Ika Puji; Wijayanti, Fitri Ayu Kusuma (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The purpose of this study was to analyze the effect of corporate social responsibility disclosure, capital structure and financial distress on stock returns. The sample is a manufacturing company listed on the IDX between 2017 and 2021. The sampling method was carried out using the convenience sampling method, namely the sample was determined with certain considerations so that 38 companies were selected. Data analysis procedure with multiple linear regression analysis. The test results show that partially, capital structure and financial distress have a positive and significant effect on stock returns; while CSR disclosure proved to have no significant effect on stock returns. Simultaneously, the three independent variables analyzed proved to have a significant effect on stock returns.